The effectiveness of individual counseling at The Majlis Agama Islam Negeri Sembilan - Othman, Mohd Hatta; Yasin, Nurhafizah Mohamad; Mohamed, Fadilah; Che Jusoh, Siti Noor Hafizah; Hamzah, Khairunnisa; Abdul Mutalib, Umi Kalthum; Hasbullah, Ahmad Syarqawi; Kamarudin, Haryati; Zakaria, Muhammad Asyraf (School of Applied Psychology, Social Work & Policy (SAPSP) Universiti Utara Malaysia (UUM) 06010 UUM Sintok Kedah, Malaysia, 2025)
This study aimed to evaluate the effectiveness of individual counseling sessions conducted by the Counseling Unit, Division of Counseling and Training, Negeri Sembilan Islamic Religious Council (MAINS) across six districts by comparing pre- and posttest scores. The instrument used was the Counseling Client Assessment Inventory (IPKK), which consists of three main domains: quality of life, cooperation, and self-change. A total of 60 respondents were selected through purposive sampling. The study employed a one-group pretest-posttest quasi-experimental design, and data were analyzed using the Wilcoxon Signed-Rank Test. The findings revealed that the self-change domain was the most consistent and statistically significant across all districts, demonstrating the effectiveness of counseling sessions in producing positive cognitive, emotional, and behavioral transformations among clients. The cooperation domain also recorded significant improvements in several districts such as Seremban, Rembau, and Port Dickson, with Tampin showing near significance; however, no notable changes were observed in Kuala Pilah and Jempol. For the quality of life domain, significant improvements were found in Rembau, Jempol, Tampin, and Port Dickson, while Seremban and Kuala Pilah showed no significant differences. Overall, this study concludes that individual counseling sessions provided by MAINS were effective in consistently improving client cooperation and self change, while the impact on quality of life requires more comprehensive, phased, and long-term interventions to achieve deeper and sustainable outcomes.